A novel three-dimensional DNA nanostructure used for thrombin detection. Issue 35 (21st August 2017) - Shu, Huawei; Mei, He; Gu, Jinxin; Yang, Yongbin; Chen, Baoguang; Huang, Ling; Wang, Qun; Chen, Xiaodong; Li, Dong; Gao, Jimin
Abstract : In this paper, a label-free electrochemical aptasensor for the detection of thrombin with high sensitivity is proposed. Abstract : In this paper, a label-free electrochemical aptasensor for the detection of thrombin with high sensitivity is proposed. A thrombin-binding capture probe (CP) was designed to form a thrombin/aptamer complex that could reduce the activity of ssDNA DNAzymes, to avoid the hydrolysis of the aptamer monolayers in the presence of thrombin. Furthermore, the presence of the CP enabled auxiliary DNA 1 (AD-1) to hybridize with auxiliary DNA 2 (AD-2) on the gold electrode (GE) and self-assemble into three-dimensional (3D) DNA networks. The electrochemical signal then originated from Ag NPs deposited in the DNA skeleton, owing to the high affinity between metal cations and DNA. Ag NPs deposited in the 3D DNA networks remarkably amplified the electrochemical signal, so as to significantly improve the sensitivity of the electrochemical aptasensor. The electrochemical aptasensor showed a linear range for thrombin detection from 0.0001 to 50 nM, with a detection limit (LOD) of 0.046 pM. Therefore, the proposed aptasensor for thrombin detection showed high sensitivity, good selectivity and excellent reproducibility, and could provide a promising sensing platform for the detection of thrombin in human serum.